La lúdica estrategia curricular para la convivencia escolar (2019)
The Ludic-pedagogical activities are of great importance for the reduction of aggressive behaviors of students. The objective of this research was to implement a recreational program for the better school coexistence of the fourth grade of the Coopteboy school of the city of Tunja. This research is part of the mixed approach, relating quantitative and qualitative data 41 through a triangulation of information-gathering instruments. The design of this project was based on the phases of action research. The unit of work was the fourth grade composed of 20 students (11 children and 9 girls) of the educational institution Coopteboy of the city of Tunja with ages between 9 and 11 years, of Strata 3 and 4, where the majority of students were characterized for being unique children. The conclusions of this research work, it is found that thanks to the Ludic program implemented, the coexistence school improved notably and that the teamwork manages to reduce the problems coexistence. It is important to modernize the educational system so that the playfulness ceases to be exclusive of the free time and is incorporated in the development of the curricular processes for a better teaching and coexistence school.